Platone allievo di Protagora? Ancora sul grande discorso del Protagora - Corradi, Michele (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
The great speech of the Protagoras (320c–328d) still leaves many questions open. Particularly striking is the presence of doctrines that later on will be taken up and further developed by Plato in such dialogues as the Politicus, the Timaeus and the Laws. For this reason, many scholars tend to think that the words of Protagoras are just a product of Plato’s invention that bear no relation to Protagoras’ actual doctrines. Nevertheless, it is possible to propose a different interpretation. At the beginning of the Protagoras (313a–314b), Socrates develops the image of the sophist as the merchant of various μαθήματα: to sell his products, the sophist praises them all indiscriminately without knowing which of them are useful and which are harmful. But he who has the ability to make this distinction can still purchase the μαθήματα from Protagoras or anyone else. Through the dialectic, Plato is able to examine them without any danger in the Protagoras and then take them up and further develop in new ways in his later dialogues.
Keywords: Myth; Dialogue; Poetry; Plato